Over or under: new phylogenetic insights in the evolution of head scratching in birds - Gutiérrez-Ibáñez, Cristián; Pellis, Vivien C.; Iwaniuk, Andrew N.; Pellis, Sergio M. (Frontiers in Ethology, 2025)
Some birds scratch their heads by moving their foot ventrally underneath their wing and others do so by moving their foot over their wing. Two competing hypotheses have been proposed to explain the distribution of these patterns. The phylogenetic hypothesis proposes that the underwing route is a novel pattern evolved in birds as the evolution of wings meant that the foot did not have to move over the front leg as is it does in quadrupeds. Consequently, the overwing route is an atavism reflecting the tetrapod ancestry of birds. The biomechanical hypothesis proposes that body morphology or environmental context determines which pattern is most effective and so explains variation across species. Earlier attempts to test these hypotheses were limited by relatively small, taxonomically biased samples of birds that did not take phylogenetic relationships into account and with few morphological traits explicitly compared. The present study includes data for 1157 species from 92% of avian families and expands the number of morphological traits compared. The most plausible ancestral state, at least for Neoaves, was overwing scratching, turning the original phylogenetic hypothesis on its head. It is also clear from the analyses that head scratching pattern is a highly labile evolutionary trait that, in some orders, repeatedly switches between over and under wing patterns. Moreover, while some morphological traits biased the likely scratching pattern used in some clades, the biomechanical hypothesis failed to predict the pattern of scratching across all birds. The most likely explanation is that the two forms of scratching are independently evolved behavior patterns and that a yet to be determined reason can switch between patterns in different lineages.